(untitled) (London Journal of Engineering Research, 2023)
Due to its great efficiency, the Plasma Physics Laboratory of the Physics Institute of the University of Brasilia (PPL/PI/UnB) has been developing Hall thrusters since 2004. Testing NeFe and SmCo permanent magnets, excellent results were achieved with the PHALL II series (PPL). However, permanent magnets have limitations due to the working temperature (determined by the Curie temperature). Therefore, it is necessary to strictly control its temperature to avoid the demagnetization effect. In this work, the results of the numerical thermal simulation were compared with experimental temperature results for the ISCT200-US Hall Thruster in order to verify the reliability of the simulation tool, allowing its future use in simulations of other Hall thrusters. Experimental temperature values and, whenever possible, dimensions and materials of the propellant components were collected from references on the ISCT200-US. A mechanical drawing of the ISCT200-US was created, a numerical thermal simulation was developed, temperature simulation values were collected and compared with experimental values. A coherent comparison was achieved, which demonstrated the reliability of the simulation tool. Such results are important for the space qualification of thrusters subsequent to the PHALL II series.